Chorein interacts with α‐tubulin and histone deacetylase 6, and overexpression preserves cell viability during nutrient deprivation in human embryonic kidney 293 cells. Issue 11 (28th July 2016) - Sasaki, Natsuki; Nakamura, Masayuki; Kodama, Akiko; Urata, Yuka; Shiokawa, Nari; Hayashi, Takehiro; Sano, Akira
ABSTRACT: The autophagy pathway has recently been implicated in several neurodegenerative diseases. Recently, it was reported that chorein‐depleted cells showed accumulation of autophagic markers and impaired autophagic flux. Here, we demonstrate that chorein overexpression preserves cell viability from starvation‐induced cell death in human embryonic kidney 293 (HEK293) cells. Subsequent coimmunoprecipitation and reverse coimmunoprecipitation assays using extracts from chorein that stably overexpressed HEK293 cells revealed that chorein interacts with α‐tubulin and histone deacetylase 6, a known α‐tubulin deacetylater and central component of basal autophagy. Indeed, acetylated α‐tubulin immunoreactivity was significantly decreased in chorein that stably overexpressed HEK293 cells. These results suggest that chorein/histone deacetylase 6/α‐tubulin interactions may play an important role in starvation‐induced cell stress, and their disruption may be one of the molecular pathogenic mechanisms of chorea‐acanthocytosis.—Sasaki, N., Nakamura, M., Kodama, A., Urata, Y., Shiokawa, N., Hayashi, T., Sano, A. Chorein interacts with α‐tubulin and histone deacetylase 6, and overexpression preserves cell viability during nutrient deprivation in human embryonic kidney 293 cells. FASEB J. 30, 3726–3732 (2016) www.fasebj.org